Blue dyed textiles in Early Iron Age Europe: Accessible or exclusive? - Hopewell, Patricia; Harris, Susanna (Archaeological Textiles Review, 2019)
Evidence for blue dyed textiles becomes widespread in Europe during the first millennium BCE. The dyestuff was likely dyer’s woad - Isatis tinctoria L. While archaeologists have done much to understand the dyeing process, archaeobotany and chemical analysis of woad dye, there remains a question as to how accessible blue colour textiles were at this time. The aim of this research is to investigate the accessibility or exclusivity of woad dyed blue textiles in this period in terms of the resources, knowledge and skills required to produce them by asking the question “how many woad plants does it take to dye 1 kg of wool yarn blue?”